Review of the competitive bid for PV in South Africa: is SA maximising job creation and value for money from its photovoltaic industy? - Mulcahy, Michael (Research of GSB, 2018)
South Africa's utility scale renewable energy industry began in earnest in November 2012. November 2012 saw the 1st round of utility scale renewable energy projects reaching financial close. These, renewable energy independent power producer, projects will be integrated into the national electricity grid and become part of South Africa's electricity generation mix. South Africa's renewable roll-out is set against a period of strong growth in the international renewable energy market particularly 2010 and 2011. The recent slowdowns in the market in Spain and Germany make South Africa highly attractive to foreign developers, financiers and suppliers. The path to reaching financial close for the first round of renewable energy project in South Africa was an uncertain one. South Africa switched from the more popular feed-in tariff (FiT) to a competitive bidding system in late 2010, causing delays and decreased confidence in the South African market. Within the new, competitive bidding programme there were complicated surety, economic development, financing and structuring requirements. These requirements reflect the myriad and sometimes unaligned goals of National Treasury, the Department of Energy (DoE), the Economic Development Department (EDD) and the Department of Trade and Industry (the dti). By the end of 2012, bids for the first two rounds of projects had been concluded, preferred bidders announced and financial close of round 1 achieved. This progress has raised questions. Were the goals of value for money and economic development attained? Are there additional areas where South Africa could improve the process to yield a more politically, socially or financially desirable result? Where is the job creation in these projects and what portions of the projects are localised? This research paper will consider the impact of the competitive bid on local manufacturing, specifically in the photovoltaic industry, and develop an understand where jobs are created along the value chain. This research paper will assess the competitiveness of locally manufactured photovoltaics? It will identify the portions of the value chain that yield high relative concentrations of jobs, and whether policy makers could design incentives and regulations that focus on the portion of the value chain which increases 'value for money' in South Africa?